Legal challenges of cross-border insolvencies in sub-saharan Africa with reference to Tanzania and Kenya: a framework for legislation and policies - Masoud, Benhajj Shaaban (Nottingham Trent University, 2012)
Although a substantial body of literature has developed in recent years in the area of cross-border insolvency, this scholarship has been dominated by scholars from the United States and Europe, so that a perspective from most of Sub-Saharan African (SSA) countries is lacking. This study addresses this perspective. It makes an in-depth examination and discussion of the challenges that SSA countries face in reform and application of cross-border insolvency law given the ever-growing multinational trade and investment. The study focuses on the risk of failure of SSA legislative processes to properly address the potential challenges of cross-border insolvencies in a manner that is sensitive to the local contexts and which provides a balance with international insolvency benchmarks. It examines cross-border insolvency theories; the global drivers for convergence of insolvency law through global insolvency norms; and the implications for cross-border insolvency regulations arising from cross-border trade and investment arrangements, such as the bilateral investment treaties, before considering the state and future of the legislative frameworks of SSA countries.
Nottingham Trent Institutional Repository (IRep) https://core.ac.uk/works/7793942/
Keywords: Cross-border Insolvency; Insolvency; International insolvency